IT'S REALLY NOT THE NOW—IT'S THE HOW!. (December 2022) - Bisk, Tsvi
In this contribution to the World Affairs 2022 Special Issue, I engage AlonBen-Meir's proposal for an Israeli–Palestinian–Jordanian Confederation previously published in this journal and discussed in depth by scholars, diplomats, and policy practitioners in a panel at the March 2022 Policy Studies Organization Middle East Dialog conference in Washington, DC. Given that achieving such a confederation has been sabotaged over and again to date, a critical question is how do we get from here to there without upsetting the irrational passions of both sides? I suggest various practical steps and policies that might mitigate the conflict in ways that could inexorably lead to the final destination of Ben-Meir's confederation .